Mapping of the current land use in part of the Irrigated Perimeter Nilo Coelho, Petrolina-PE, Brazil - Ramos, Ricardo Rivelino Dantas; Melo Júnior, Júlio César Ferreira de (Comunicata Scientiae, 2019)
The objective of this study was to quantify and spatialize the agricultural composition and current land use in part of the Irrigation perimeter Nilo Coelho from the Landsat 8 satellite digital image classification. At first we performed the unsupervised classification image related to January 2014, identifying the separability within natural vegetation, water bodies, agricultural crops and anthropized areas. Then the supervised classification Maxver model was performed where it was observed that the fruit classes “Grape” (5.41%) “Acerola” (3.75%), “Coconut” (6.14%) “Guava” (6.17%), “Banana” (2.29%) and “Mango” (8.18%) showed dominance in the study area. These classes stood out in terms of yield in the area, pointing out that in that expansion which occurs in an area with agricultural crops in the irrigated Nilo Coelho, crops of mango, coco, guava, acerola, banana and grape also grow. In addition, we observed the emergence of new areas with passion fruit crops, melon, watermelon, corn, beans, onions, pumpkin, sweet potatoes, tomatoes, bell peppers, among other crops. Furthermore, we also found the occurrence of pastures containing buffel and elephant grasses, intercropping or not. The estimated overall accuracy was 80.52%, and the mapping defined as very good, with Kappa index equal to 0.7783.